Comparison of ultrasound-guided joint reduction with traditional methods in the emergency center - Eriten, Semih; İzci, Vedat and Menekşe, Serdar (The European Research Journal, 2025)
Objectives: This study aimed to compare and analyze the reliability of ultrasound-guided procedures and traditional methods in the reduction of joint dislocations in the emergency department. Methods: A total of 136 cases were included in the prospective randomized controlled study. The cases were randomized into groups as ultrasound-guided reduction (n=66) and traditional reduction (n=70). The reduction success, time spent for the procedure, complication rates, pain scores and patient satisfaction levels were evaluated. Functional results and osteoarthritis development were also analyzed in long-term follow-up. Chi-square test, Student t-test and Mann-Whitney U test were used in the statistical analysis of the data. Results: The success rate in the ultrasound reduction group (93.9%) was significantly higher than in the conventional reduction group (71.4%) (P<0.001). The mean reduction time was calculated as 3.2±1.8 minutes in the ultrasound group and 7.6±4.1 minutes in the conventional group (P<0.001). Complication rates were 7.6% in the ultrasound group and 21.4% in the conventional group (P=0.018). While 90.9% anatomical position was achieved in the ultrasound group in post-reduction, this rate remained at 64.3% in the conventional group (P<0.001). In the long-term follow-up, osteoarthritis development (ultrasound: 15.2%, conventional: 35.7%, P=0.012) and functional limitation rates (ultrasound: 10.6%, conventional: 25.7%, P=0.021) were significantly lower in the ultrasound group. Conclusions: Ultrasound-guided interventions in the reduction of joint dislocations in the emergency department provide higher success rates, shorter treatment times, and lower complication rates than traditional methods. Long-term results also support the superiority of reductions performed with ultrasound guidance. In light of these findings, ultrasound-guided reduction is recommended as the first-line approach in the management of joint dislocations.